2006
DOI: 10.1152/ajpheart.00404.2006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced α1-adrenergic trophic activity in pulmonary artery of hypoxic pulmonary hypertensive rats

Abstract: . Enhanced ␣1-adrenergic trophic activity in pulmonary artery of hypoxic pulmonary hypertensive rats. Am J Physiol Heart Circ Physiol 291: H2272-H2281, 2006. First published June 23, 2006 doi:10.1152/ajpheart.00404.2006.-Mechanisms that induce the excessive proliferation of vascular wall cells in hypoxic pulmonary hypertension (PH) are not fully understood. Alveolar hypoxia causes sympathoexcitation, and norepinephrine can stimulate ␣1-adrenoceptor (␣1-AR)-dependent hypertrophy/hyperplasia of smooth muscle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 45 publications
(137 reference statements)
1
29
0
Order By: Relevance
“…In support of this hypothesis, we recently found that NE stimulates ␣ 1 -AR-dependent growth of the rat pulmonary artery maintained in organ culture (12). Furthermore, this effect was significantly augmented in pulmonary arteries obtained from animals with hypoxic PH.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…In support of this hypothesis, we recently found that NE stimulates ␣ 1 -AR-dependent growth of the rat pulmonary artery maintained in organ culture (12). Furthermore, this effect was significantly augmented in pulmonary arteries obtained from animals with hypoxic PH.…”
mentioning
confidence: 56%
“…Besides growth factor receptor tyrosine kinases, e.g., BMP receptor 2, angiopoietin/Tie2, PDGF␤ receptor, and heparinbinding-EGF/EGF receptor (ErbB1), several G protein-coupled receptor ligands with trophic activity have also been implicated in PH, including serotonin and its transporter and endothelin-1 (7,17,21,22,26,27,33). Catecholamines have also been proposed to contribute to PH (12,29,31,32). Stimulation of certain ␣ 1 -adrenoceptor (␣ 1 -AR) subtypes by norepinephrine (NE) induces growth of VSMCs and adventitial fibroblasts (discussed below).…”
mentioning
confidence: 99%
“…10,12,15,21 NO is the primary mediator of vasodilation that is released from the vascular endothelium. …”
Section: Discussionmentioning
confidence: 99%
“…10,12,15,21 NO is the primary mediator of vasodilation that is released from the vascular endothelium. NO released toward the vascular lumen is a potent inhibitor of platelet aggregation 22 and exerts anti-inflammatory effects by inhibiting leukocyte adhesion to the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Ishimitsu et al [35] demonstrated in a clinical study that Olm combined with Azl suppressed heart rate, inflammation, and oxidative stress. Meanwhile, catecholamines directly increase NAD(P)H oxidase activity by stimulating ␣ 1 -and ␤ 2 -receptors [36,37] . ␤ 1 -Receptor antagonists improve endothelial function and reduce vascular oxidative stress by NAD(P)H oxidase [38] .…”
Section: Discussionmentioning
confidence: 99%